A randomised preclinical trial of adrenaline use during cardiac arrest in mice - Daniel G. Donner; Jason E. Bloom; Waled A. Shihata; Aascha A. Brown; Rosalind Cook; Tsin Yee Tai; Gavin W. Lambert; Po-Yin Chu; William Chan; Dion Stub; Bing H. Wang; David M. Kaye (Resuscitation Plus, 2022)
Background: Adrenaline is routinely administered during cardiac arrest resuscitation. Using a novel murine model of cardiac arrest, this study evaluates the effects of adrenaline use on survival and end-organ injury. Methods: A total of 58 mice, including cardiac arrest (CA) and sham (SHAM) groups received intravenous potassium chloride either as a bolus (CA) or slow infusion (SHAM), inducing ECG-confirmed asystole (in CA only) for 4-minutes prior to intravenous adrenaline (+ADR;250 ul,32 ug/ml) or saline (-ADR;250 ul) and manual chest compressions (300 BPM) for 4-minutes. Mice with return of spontaneous circulation (ROSC) were assessed at 24- or 72-h timepoints. Results: Among animals that underwent CA, rates of ROSC (n = 21 (95 %) vs n = 14 (82 %), P = 0.18) and survival to the planned endpoint (n = 11 (50 %) vs n = 12 (71 %), P = 0.19) were similar when comparing those treated with (CA+ADR) and without (CA-ADR) adrenaline. However, in CA animals that initially achieved ROSC, subsequent mortality was approximately 3-fold greater with adrenaline treatment (48 % vs 14 %, P = 0.042). Among SHAM animals, adrenaline use had no impact on survival rates or other endpoints. Greater myocardial injury occurred in CA+ADR vs CA-ADR, with increased Hs-Troponin levels measured at 24- (26.0 ± 0.9 vs 9.4 ± 5.3 ng/mL, P = 0.015) and 72-h (20.9 ± 8.3 vs 5.0 ± 2.4 ng/mL, P = 0.012), associated with increased expression of pro-inflammatory and fibrotic genes within cardiac and renal tissue. Conclusion: Adrenaline did not improve ROSC or overall survival but following successful ROSC, its use resulted in 3-fold greater mortality rates. Adrenaline was also associated with increased myocardial injury, end-organ inflammation, and fibrosis. These findings underscore the need for further preclinical evaluation of alternate pharmacologic adjuncts for cardiopulmonary resuscitation that improve survival and limit end-organ injury.